Human Resource Development Model Based on Local Wisdom Tri Kaya Parisudha in Dealing with Globalization - I Ketut Marta Atmaja (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis study aims to determine the model of human resource development based on local wisdom with good ethics in the Hindu religion (Vedas) in life and in society (Tri Kaya Parisudha) in the face of globalization. The development of human resource as a process to cultures country is purposed to increase the quality of Balinese people who’s mastered the knowledge, skill, competence and concept which are appropriate to the recent development of science and technology. The concept which is required in this century, such as the competenceconcept to look forward, the concept of quality and wealthy, and the concept of change which have to be appropriate to the society’s values. The human resource is developed based on an assumption that every human has a potential resource which its border cannot be determined easily. Therefore, the human isthe most important as the subject and more than other elements to reach a certain goal. The development ofhuman resource is also as an effort to increase human’s technical competence, theoretical competence, conceptual competence, as well as personal attitude which is appropriate to the needs of a profession and position througheducation.Education based on local wisdom can be used as a media to conserve the potency of every region. The potency of a region is a potency of specific resource which is owned by a certain region, moreover, it can be a precious contribution to the regional activities in developing human resource in the international level. Furthermore, the students in Bali required to use Tri Kaya Parisudha as the reference to guide their competence to be a great human resource for Indonesian Country.This reserach has links to results with theoretical implications and practical implications for school management and a model of human resource development with proper and correct local wisdom in educational how to practice Hinduism in life and in society. Research this limitation still needs improvement, research is still needed to make other research in subsequent research. Globalization of global uniqueness, which together challenges and reforms the community, especially in the form of a modern state.